Ultra‐deep desulfurization of a model fuel using novel VOHPO4 0.5H2O/boehmite catalysts. (10th April 2019) - Najafi Chermahini, Alireza; Moslemi, Ali; Mohammadnezhad, Gholamhossein
Abstract : A high‐surface‐area boehmite was used as the support for a series of vanadium phosphate catalysts. The catalysts were prepared by heating of V2 O5 in an isobutyl alcohol and benzyl alcohol mixture at 140°C for 5 h to reduce V 5+ to more active V 4+ in the presence of phosphoric acid. Then a series of catalysts with various VPO loadings on boehmite were synthesized. The catalysts were characterized using various techniques. The catalysts were utilized for extraction combined with catalytic oxidation of dibenzothiophene. The important factors influencing the desulfurization process, including reaction time, temperature, H2 O2, catalyst loading, catalyst amount and solvents, were systematically investigated. Under the optimized reaction conditions, i.e. 30 mg of catalyst loading at 50°C and in 60 min, sulfur removal reached 94%. The catalyst was recycled and reused five times. Abstract : Boehmite with high surface area was prepared through a novel method and characterized. Vanadium hydrogen phosphate as a catalyst was supported on the boehmite at various loadings. The catalysts were used for extractive oxidative desulfurization of a model fuel. Under optimum conditions, dibenzothiophene removal reached 94%.